2023
DOI: 10.1186/s12879-023-08028-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for Kaposi’s Sarcoma associated herpesvirus among men who have sex with men in Shanghai, China

Abstract: Background This study aimed to facilitate the understanding of the transmission route and risk factors that might contribute to the infection of Kaposi’s sarcoma associated herpesvirus (KSHV) among men who have sex with men (MSM). Methods A cross-sectional study of 520 subjects was conducted in Shanghai, China in 2020. Plasma samples were collected and screened for KSHV, HIV, HBV, HCV, and syphilis. Univariate and multivariate logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In a recent Chinese study among 520 individuals more male sex partners, lower income and being a student were associated with higher seropositivity for HHV-8. In addition being coinfected with hepatitis C virus and syphilis resulted in higher risk for seropositivity [9]. This higher seropositivity has been attributed to the more frequent use of saliva as a lubricant in homosexual practices as saliva is the main HHV-8 focus [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent Chinese study among 520 individuals more male sex partners, lower income and being a student were associated with higher seropositivity for HHV-8. In addition being coinfected with hepatitis C virus and syphilis resulted in higher risk for seropositivity [9]. This higher seropositivity has been attributed to the more frequent use of saliva as a lubricant in homosexual practices as saliva is the main HHV-8 focus [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…For extensive disease, a combination of surgery, chemotherapy and radiation is advocated. Some recent therapeutic agents such as imatinib and matrix metalloproteinase inhibitors are also being tried 27 , 28 , 29 and some antiviral agents including ganciclovir, foscarnet, valganciclovir and cidofovir have been shown to have some therapeutic effects via inhibiting HHV‐8. 30 , 31 However, the best therapeutic approach for KS lesions in setting of PV is still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, earlier studies have found increased risk of KS also in MSM without HIV [ 25 , 26 ]. This may reflect a high seroprevalence of HHV-8 among MSM [ 27 ], which has been associated with high-risk sexual behavior and multiple sexual partners [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%